New findings of Neogene Xenarthra (Mammalia) from Ecuador : diversity and perspective - Zurita, Alfredo Eduardo (2019)
Fil: Zurita, Alfredo Eduardo. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.